2021
DOI: 10.1016/j.cmi.2020.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for candidaemia in hospitalized patients with liver cirrhosis: a multicentre case–control–control study

Abstract: The aim of this study was to evaluate the risk factors for candidaemia in patients with liver cirrhosis. Methods: This was a caseecontrolecontrol (1:2:2) study performed in four Italian tertiary centres from 2006 to 2015. Cases were patients with liver cirrhosis developing candidaemia. For every case of candidaemia we enrolled two additional patients undergoing blood cultures for suspected infection yielding isolation of a bacterial pathogen (control A) and two additional patients undergoing blood cultures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
3
34
1
Order By: Relevance
“…These organisms can migrate across the intestinal wall to disseminate. In our study patients, it was found that the long-term use of broadspectrum antibiotics and neutropenia was independently related to fungal infection, which was consistent with recent studies [9,12,14,15]. Of the 36 confirmed IPFI cases, Candida albicans infection was the most frequent pathogens in HBV-ACLF patients, accounting for 44.44% (16/36), followed by Aspergillus 33.33% (12/36), and Candida glabrata 11.11% (4/36).…”
Section: Discussionsupporting
confidence: 93%
“…These organisms can migrate across the intestinal wall to disseminate. In our study patients, it was found that the long-term use of broadspectrum antibiotics and neutropenia was independently related to fungal infection, which was consistent with recent studies [9,12,14,15]. Of the 36 confirmed IPFI cases, Candida albicans infection was the most frequent pathogens in HBV-ACLF patients, accounting for 44.44% (16/36), followed by Aspergillus 33.33% (12/36), and Candida glabrata 11.11% (4/36).…”
Section: Discussionsupporting
confidence: 93%
“…In previous research, rifaximin treatment effects were shown to decrease the risk of recurrent encephalopathy [61]. Patients with cirrhosis who developed candidemia also were shown with a lower rate of candidemia when treated with rifaximin [62]. Cirrhotic patients with refractory ascites when given rifaximin were associated with mitigated ascites and increased survival [63].…”
Section: Cirrhosis and Antibioticsmentioning
confidence: 92%
“…In previous research, rifaximin treatment effects were shown to decrease the risk of recurrent encephalopathy [32]. Patients with cirrhosis who developed candidemia also were shown with a lower rate of candidemia when treated with rifaximin [33]. Cirrhotic patients with refractory ascites when given rifaximin were associated with mitigated ascites and increased survival [34].…”
Section: -1 Cirrhosis and Antibioticsmentioning
confidence: 92%